STUDI PENGUJIAN KADAR LUMPUR AGREGAT HALUS PADA PASIR DI KOTA BATAM - Mahfuz Hudori; Marvin Tandedi; Aldy Tri Sentanu; Mohammad Adolf Ferdinand (Racic : Rab Construction Research, 2022)
Clay is one of the parameters that need to be tested before fine aggregates is used in construction. According to SNI 03-1750-1990, the limit of clay in fine aggregate is 5%. This study aims to determine the clay levels in the sand in Batam City. Clay levels data were analyzed using the one-sample t-test of statistical method. The results of the analysis show that the clay levels in the sand in Batam City is more than 5%, so that the sand in Batam City has not been fully used as fine aggregate for construction.